Moral Educational Values In The Book Al-Azkar By Imam An-Nawawi Ad-Dimasyqi - Ahmad Nawawi; Zulheddi Zulheddi; Azizah Hanum OK (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the content of al-Azkar and to identify the moral educational values contained within it, as well as to examine its relevance to modern Islamic education. This research employs a qualitative approach with a library research design. The primary data source is the book al-Azkar by Imam an-Nawawi ad-Dimasyqi, which is analyzed using the content analysis method to uncover the moral educational values embedded in the text. The findings indicate that al-Azkar contains hadiths of the Prophet Muhammad Saw related to daily practices of dhikr and supplication, which are rich in moral educational values. These values include: (1) morals toward Allah Saw such as tawhid (monotheism), piety, sincerity, gratitude, patience, trust in God (tawakkul), and repentance; (2) morals toward the Prophet Saw in the form of respect and love; (3) morals toward fellow human beings such as devotion to parents, respect for teachers, and maintaining good relationships within family and society; (4) inner morals such as humility (tawadu’), cooperation (ta’awun), tolerance (tasamuh), and positive thinking (husn al-?ann); and (5) morals toward other creatures, including ethical treatment of animals.